1998
DOI: 10.1074/jbc.273.49.32895
|View full text |Cite
|
Sign up to set email alerts
|

Shigella-induced Apoptosis Is Dependent on Caspase-1 Which Binds to IpaB

Abstract: We report here that the Shigella invasion plasmid antigen (Ipa)B, which is sufficient to induce apoptosis in macrophages, binds to caspase (Casp)-1, but not to Casp-2 or Casp-3. Casp-1 is activated and its specific substrate interleukin-1␤ is cleaved shortly after Shigella infection. Macrophages isolated from Casp-1 knock-out mice are not susceptible to Shigella-induced apoptosis, although they respond normally to other apoptotic stimuli. Shigella kills macrophages from casp-3, casp-11, and p53 knock-out mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
295
0
9

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(313 citation statements)
references
References 47 publications
9
295
0
9
Order By: Relevance
“…However, the activation of caspase-1 does not appear to be the only mechanism required for the chlamydia-induced secretion of IL-18 because similarly infected fibroblast cells did not secrete detectable levels of IL-18 despite the activation of caspase-1. Other studies have suggested that the Shigella invasion plasmid Ag B and Salmonella invasion protein B directly bind to caspase-1 and trigger hydrolysis of this cysteine protease into its bioactive forms, which then cleave pro-IL-1␤ and trigger host cell apoptosis (33,34). Although little is known about the subcellular sites and detailed mechanisms responsible for activation of caspase-1 (35-37), we observed that TPCK and lactacystin, two structurally different but specific inhibitors of proteasomes, significantly inhibited IL-18 production induced by chlamydia infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, the activation of caspase-1 does not appear to be the only mechanism required for the chlamydia-induced secretion of IL-18 because similarly infected fibroblast cells did not secrete detectable levels of IL-18 despite the activation of caspase-1. Other studies have suggested that the Shigella invasion plasmid Ag B and Salmonella invasion protein B directly bind to caspase-1 and trigger hydrolysis of this cysteine protease into its bioactive forms, which then cleave pro-IL-1␤ and trigger host cell apoptosis (33,34). Although little is known about the subcellular sites and detailed mechanisms responsible for activation of caspase-1 (35-37), we observed that TPCK and lactacystin, two structurally different but specific inhibitors of proteasomes, significantly inhibited IL-18 production induced by chlamydia infection.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of caspase-1 has mostly been implicated in inflammatory responses; however, its implication in apoptotic processes has also been documented (Hilbi et al, 1998;Liu and Abrams, 2003). In Fas-induced apoptosis, the activation of the primarily inflammation associated caspase-1 and -4 provides an amplification loop to enhance apoptosis, a function that has often been implicated in pathways involving caspase-1 activation.…”
Section: Activation and Processing Of Ceacam1 During Apoptosis S Nittmentioning
confidence: 99%
“…However, some virulent bacteria are able to evade killing by macrophages and actually induce macrophage death. It is known that the mechanism of macrophage death induced by different pathogens varies [11][12][13][14]. Bacterial endotoxin (lipopolysaccharide; LPS) is a complex glycolipid found in the outer membrane of all gram-negative bacteria, and is believed to play a crucial role in induced cellular responses to gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%